The Internalisasi nilai-nilai pendidikan karakter melalui mata kuliah Pendidikan Agama Islam dan Pendidikan Pancasila - Yayah, Yayah Nurasiah; Andriyana; Zainul Hakim (Politeknik Negeri Bengkalis, 2023)
The internalization of character education values through the courses of Islamic Religious Education and Pancasila Education is important for the students of the State Polytechnic of Creative Media. This is because character is a crucial aspect in the personal development of individuals to achieve success in the future. Islamic Religious Education and Pancasila Education are utilized as means to shape the character of students by introducing the moral and ethical values within them. Such education helps students understand the significance of strengthening values like integrity, responsibility, honesty, justice, and a strong work ethic. The method employed is literature review with a qualitative approach, collecting data from scholarly journals, books, relevant online sources, as well as through direct observation via interviews and questionnaire surveys. In facing future challenges, students of the State Polytechnic of Creative Media are required to possess a strong character and good moral integrity. Therefore, the internalization of character education values through Islamic Religious Education and Pancasila Education courses becomes essential to support future success. In this teaching process, the participation and responsibility of lecturers and teaching staff are also necessary in providing a solid understanding of these character values to the students. This way, students will be able to integrate these values into their daily lives and become individuals with good character. Keywords: Character Education, Islamic Religious Education, Pancasila Education